Insight Into Disorder, Stress and Strain of Radiation Damaged Pyrochlores: A Possible Mechanism for the Appearance of Defect Fluorite - Finkeldei, Sarah C.; Chang, Shirley; Ionescu, Mihail; Oldfield, Daniel; Davis, Joel; Lumpkin, Gregory R.; Simeone, David; Avdeev, Max; Brandt, Felix; Bosbach, Dirk; Klinkenberg, Martina; Thorogood, Gordon J. (Frontiers in Chemistry, 2021)
We have examined the irradiation response of a titanate and zirconate pyrochlore - both of which are well studied in the literature - in an attempt to define the appearance of defect fluorite in zirconate pyrochlores. Conditions of approximately 1 displacement per atom He2+ were used to simulate long term waste storage conditions as outlined by previous results from Ewing (Ewing, 1999) in a large enough sample volume to allow for neutron diffraction, as not attempted previously. Firstly, the titanate sample used a baseline comparison pyrochlore due to the fact that it readily becomes amorphous under these conditions behaved as expected. In contrast, the zirconate pyrochlore builds up tensile stress in the absence of detectable strain. This might be the mechanism of lanthanide zirconate pyrochlores responding to radiation damage due to the grains breaking into even smaller diffraction domains, thus creating a diffraction pattern with the appearance of defect fluorite as per Simeone et al. (D. Simeone et al., 2019). An (ErNd)2(ZrTi)2O7 pyrochlore was synthesized in an attempt to make a solid solution sample of the zirconate and titanate to examine which mechanism would dominate. Although strain was detected in the pristine sample it was not of sufficient quality to perform a full analysis on.